1998
DOI: 10.1038/ng0298-118
|View full text |Cite
|
Sign up to set email alerts
|

Mice with gene targetted prion protein alterations show that Prnp, Sine and Prni are congruent

Abstract: Classical genetic analysis has identified Sinc/Prni as the major gene controlling mouse scrapie incubation time. Sinc/Prni is linked to Prnp, the gene encoding the prion protein (PrP). Prnp alleles express distinct PrP protein variants, PrP A and PrP B, which arise from codon 108L/F and 189 T/V dimorphisms. Prnp genotype segregates with incubation time length which suggests, but does not prove, that incubation time is controlled by PrP dimorphisms, and that the Sinc/Prni and Prnp loci are congruent. We have us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 48 publications
2
106
0
2
Order By: Relevance
“…The results of Houston et al (2002) indicate differences in average incubation period among different genotypes for Cheviot and Dorset animals that were infected artificially by a subcutaneous inoculation with SSBP/1. In addition, Moore et al (1998) found an association between the genotype of PrP and incubation period in mice.…”
Section: Effect Of Prp Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…The results of Houston et al (2002) indicate differences in average incubation period among different genotypes for Cheviot and Dorset animals that were infected artificially by a subcutaneous inoculation with SSBP/1. In addition, Moore et al (1998) found an association between the genotype of PrP and incubation period in mice.…”
Section: Effect Of Prp Genotypementioning
confidence: 99%
“…It has also been demonstrated that there is an interaction between the genotype of the host and the scrapie strain (Goldmann et al, 1994;O'Rourke et al, 1997; Barron et al, 2003). In the mouse, the incubation period of the disease has been associated with the PrP genotype (Moore et al, 1998) and with the prion strain inoculated (Bruce et al, 1991). However, polymorphism of the Prnp gene does not explain the total variation in incubation period that is observed, indicating the existence of other environmental and genetic factors that are involved in the disease.…”
mentioning
confidence: 99%
“…The PrP gene is identical to the scrapie incubation period (Sip) gene (Dickinson & Outram, 1988 ;Moore et al, 1998). In all breeds studied, an amino acid change from glutamine (Q) to arginine (R) at codon 171 in the PrP gene renders the animal more resistant towards natural and experimental scrapie as well as experimental bovine spongiform encephalopathy , and only a single case of scrapie has been reported in sheep with a homozygous RR "(" PrP genotype (Ikeda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic of TSE is the accumulation of PrP sc (pathological protease-resistant isoform), which is generated as a result of post-translational modification and changed in the stereochemical conformation of host-encoded, cellular prion proteins (PrP c ) (Prusiner 1998). According to reports, the polymorphisms of PRNP have been shown to influence incubation and the susceptibility of these diseases such as BSE and the incubation period in humans (Shibuya et al 1998;Shi et al 2016), mice (Moore et al 1998;Aguilar-Calvo et al 2014), goats (Vitale et al 2016), sheep (Stepanek and Horin 2017) and buffaloes (Yaman et al 2017).…”
Section: Introductionmentioning
confidence: 99%